IMPACT ON QUALITY OF LIFE IN PATIENTS WITH KNEE OSTEAOARTHRITIS IN FAISALABAD - Muhammad A wais Mujahid; Muhammad Junaid Azam; Abdul Salam et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: There are many researches present in Pakistan and other countries on quality of life inpatients of knee osteoarthritis. AIMS & OBJECTIVES: To analyze the quality of life aﬀected in patients due to knee osteoarthritis and to see the association between pain in walking and physical function variable by using Womack scale. METHODOLOGY: Patients from 40 to 65 years were included in this study as per inclusion criteria. This is cross-sectional study. Simple convenient sampling technique is being used. Sample size is 138. Patients with grade 3 knee osteoarthritis were included, diagnosed as per criteria of Kellgren and Lawrence grading scale. Data collected by using Womack scale from Allied hospital, District headquarter hospital (DHQ), Madinah teaching hospital (MTH) and Physiotherapy clinics the University of Faisalabad. RESULTS: The total Womack score of 138 patients was collected, 20 patients reported of having less than 35% aﬀected quality of life and 80reported in between 35%-50%, 29 reported in between 50%-65% and 9 show severe and above 65% aﬀected quality of life and cause diﬃculty in performing activities of daily living. Majority of patients have up to 50% aﬀected quality of life. There is also a strong association between pain in walking and physical function variables of Womac scale. CONCLUSION: Patients with grade 3 knee osteoarthritis have aﬀected quality of life. Pain in walking and physical function is associated with each other, and alpha was less than 0.05 so it was concluded that physical function variables are signiﬁcantly associated with pain during walking.